2021
DOI: 10.1002/cnr2.1394
|View full text |Cite
|
Sign up to set email alerts
|

Surface expression of the immunotherapeutic target GD2 in osteosarcoma depends on cell confluency

Abstract: Background: Chimeric antigen receptor (CAR) T-cell therapy of pediatric sarcomas is challenged by the paucity of targetable cell surface antigens. A candidate target in osteosarcoma (OS) is the ganglioside G D2 , but heterogeneous expression of G D2 limits its value. Aim:We aimed to identify mechanisms that upregulate G D2 target expression in OS.Methods and results: G D2 surface expression in OS cells, studied by flow cytometry, was found to vary both among and within individual OS cell lines. Pharmacological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…IL-18 TRUCKs show higher toxicities against high GD 2 -expressing target cells confirming the in vitro studies by Wiebel et al. ( 52 ).…”
Section: Discussionsupporting
confidence: 84%
“…IL-18 TRUCKs show higher toxicities against high GD 2 -expressing target cells confirming the in vitro studies by Wiebel et al. ( 52 ).…”
Section: Discussionsupporting
confidence: 84%
“…Recently, it has been reported in Ewing sarcoma ( 31 ), neuroblastoma ( 27 ), and lung cancers ( 15 ), that the EZH2 inhibitor tazemetostat, selectively and reversibly, induces GD2 surface expression without altering cell viability. However, inhibition of the histone methyltransferase EZH2 failed to increase GD2 expression in osteosarcoma cell lines ( 47 ). In a phase I/II trial (NCT01897571) for patients with advanced solid tumors, the recommended pediatric phase II dose of tazemetostat was determined to be 800 mg twice daily ( 48 ), with tolerable adverse events most frequently (>15%), including asthenia, anemia, anorexia, muscle spasms, nausea, and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been noted that hypoxic conditions led to overexpression of the key enzyme to GD2 production, ST8SIA1, in colon tumor cell lines ( Yin et al, 2010 ). Similarly, osteosarcoma spheroids had gradually increased GD2 expression over time, concurrent with cell growth and densification of the sphere causing a decrease in oxygen availability ( Wiebel et al, 2021 ). Further studies are required to confirm the link between hypoxia and GD2 expression.…”
Section: Gd2 Expression In Cancermentioning
confidence: 99%
“…In a more technical approach, but particularly relevant to the use of 2D and 3D in vitro models, it has been demonstrated that cell confluency modulates GD2 expression, whether in monolayer or spheroid culture ( Wiebel et al, 2021 ). If unchecked, this parameter may negatively impact data reproducibility.…”
Section: Gd2 Expression In Cancermentioning
confidence: 99%
See 1 more Smart Citation